A review of anatomical, physiological, biological characteristics and uses of Plectranthus neochilus - Ramborger, Bruna Piaia; Paz, Maria Elisabeth Gomes; Denardin, Elton Luiz Gasparoto; Soares, Jefferson de Jesus; Roehrs, Rafael (Ciência e Natura, 2020)
Plectranthus neochilus’ tea is widely used for medicinal purposes like digestive disorders, liver problems, hangover and to a lesser extend, for treating respiratory infections. It is one type of “boldo” used in different corners of the world because it has a year-round growth, easy adaptation and environmental resistance, tolerating intense sun and demanding little manipulation. This review aims to compile the up-to-date information about P. neochilus obtained from scientific databases (ScienceDirect, Springer, Google Scholar and PubMed). The plant was recently identified and differentiated anatomically and microscopically from anothers also called “boldo”. Many compounds were identified in their extracts (aqueous, ethanolic, hexane among others). The most recent studies point out the importance of its essential oil, rich in mono and sesquiterpenes. Some activities presented by these extracts or essencial oil are: antioxidant, insecticidal, antibacterial, antifungal, anticancer and antischistosomal activity. In relation to the non-traditional use of the plant, it is used to promote phytoremediation or to be used in green roof. P. neochilus has versatility use and high valuable biological character therefore, more studies are necessary with more extracts and formulations of their oil in order to verify activities in different experimental models.